Students' Engagement in Learning English Vocabulary using Audiovisual Games in Junior High School - Nur Azkiyah, Sarah; Pujiawati, Nia; Kamil, Acep Bahrum (Universitas Pahlawan Tuanku Tambusai, 2024)
This study investigates student engagement in learning English vocabulary using Kahoot!, an interactive audiovisual gaming platform as a teaching tool in middle school. The subjects in this study are eighth-grade students in the class in the second semester of the academic year 2023-2024. Through classroom observations and in-depth interviews with students, the research explores four dimensions of engagement: emotional, behavioral, cognitive, and agentic. The study finds that Kahoot! effectively enhances student engagement in learning English vocabulary. Students responded positively to Kahoot!, expressing initial excitement, enthusiasm, and motivation in vocabulary learning. They appreciated Kahoot!'s interactive and enjoyable nature, facilitating active participation and friendly competition among classmates. Moreover, Kahoot! aids in improving vocabulary comprehension and retention through audiovisual elements and interactive quizzes. Students also valued the platform for its flexibility, allowing for both independent learning and collaborative activities. Overall, Kahoot! is found not only to boost motivation but also to create a lively classroom environment that is supportive and effective. This research underscores the potential of educational technology like Kahoot! in transforming traditional learning approaches into dynamic and engaging experiences tailored to various learning styles and preferences.